Energy Storage Equipped STATCOM for Power Quality Improvements in Distribution Grids. Impact of Load Dynamics on System Performance. - Weidenmo, Viktor (My University, 2012)
Increasing awareness and concerns regarding unacceptable power quality are causing a growing interest in custom power devices, used to improve power quality on distribution level. One of the most interesting types of custom power devices, due to its exibility and fast control, is the shunt-connected voltage source converter (VSC), also known as the static synchronous compensator (STATCOM). This thesis deals with the control, performance and applications of STATCOMs equipped with energy storage for power quality improvements. The additional power quality applications, made possible by the energy storage, include a more complete mitigation of voltage dips. Furthermore, the energy storage also enables a STATCOM to support an entry into islanding operation, by rapid balancing of loads, after tripping of a single feeder. The final part in the thesis treats dynamic loads and their impact on system performance. Dynamic loads of this type are not common in the power system today, but might be in the future. Using state space analysis and simulations, it is shown that dynamic loads can cause serious stability problems in power systems and that STATCOMs without energy storages might even worsen this effect. It is further shown that STATCOMs equipped with energy storages, due to the ability of controlling both active and reactive power, can keep the system performance practically unaffected during the same conditions.
Keywords: Elkraftteknik; Electric power engineering